Rectus Abdominis Muscle Malignant Fibrous Histiocytoma Causing a Large Abdominal Wall Defect: Reconstruction with Biological Mesh - Evangelos Falidas; Stavros Gourgiotis; Christina Goudeli; Stavros Mathioulakis; Konstantinos Vlachos; Constantinos Villias (Case Reports in Surgery)
Malignant fibrous histiocytoma (MFH) is a common soft tissue sarcoma usually involving limbs and retroperitoneum. MFH of the rectus abdominis muscle is extremely rare. Surgery in similar cases leads to large abdominal wall defects needing reconstruction. Biological and synthetic laminar absorbable prostheses are available for the repair of hernia defects in the abdominal wall. They share the important feature of being gradually degraded in the host, resulting the formation of a neotissue. We herein report the case of an 84-year-old man with MFH of the rectus abdominis muscle which was resected and the large abdominal wall defect was successfully repaired with a biological mesh.